Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Opposite changes in the expression of clathrin and caveolin-1 in normal and cancerous human prostate tissue: putative clathrin-mediated recycling of EGFR - Boyu Xie; Hawra Zuhair; Rui Henrique; Michael Millar; Timothy Robson; Christopher Thrasivoulou; Kerry Dickens; Jane Pendjiky; Asif Muneer; Hiten Patel; Aamir Ahmed (Histochemistry and Cell Biology, 2023)
Endocytosis, an important macromolecule uptake process in cells, is known to be dysregulated in cancer. Clathrin and caveolin-1 proteins play a major role in receptor-mediated endocytosis. We have used a quantitative, unbiased and semi-automated method to measure in situ protein expression of clathrin and caveolin-1 in cancerous and paired normal (cancer adjacent, non-cancerous) human prostate tissue. There was a significant ( p < 0.0001) increase in the expression of clathrin in prostate cancer samples ( N = 29, n = 91) compared to normal tissue ( N = 29, n = 67) ( N = number of patients, n = number of cores in tissue arrays). Conversely, there was a significant ( p < 0.0001) decrease in expression of caveolin-1 in prostate cancer tissue compared to normal prostate tissue. The opposite change in expression of the two proteins was highly correlated to increasing cancer aggressiveness. There was also a concurrent increase in the expression of epidermal growth factor receptor (EGFR), a key receptor in carcinogenesis, with clathrin in prostate cancer tissue, indicating recycling of EGFR through clathrin-mediated endocytosis (CME). These results indicate that in prostate cancer, caveolin-1-mediated endocytosis (CavME) may be acting as a brake and increase in CME may facilitate tumorigenicity and aggressiveness of prostate cancer through recycling of EGFR. Changes in the expression of these proteins can also potentially be used as a biomarker for prostate cancer to aid in diagnosis and prognosis and clinical decision-making.

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)